2020
DOI: 10.1007/s10509-020-03816-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Galactic sources of high-energy neutrinos

Abstract: High-energy neutrinos present the ultimate signature for a cosmic ray accelerator. Galactic sources responsible for acceleration of cosmic rays up to the knee in cosmic ray spectrum will provide a guaranteed, albeit subdominant, contribution to the high-energy cosmic neutrino flux. In this review, we discuss the the prospects for identification of high-energy neutrinos from sources of the very high energy gamma ray emission in the Milky Way. We present the status of the search for point-like and extended emiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 157 publications
0
8
0
Order By: Relevance
“…There are contributions on the production of cosmic ray (CR) electrons (Alsaberi et al 2019) and their transport (Heesen 2021) as deduced from observations, the generation of X-rays and cosmic γ -rays in interstellar shocks (Sano and Fukui 2021), the mechanism of particle acceleration via diffuse shock acceleration (Urošević et al 2019), the thermal and non-thermal X-ray emission from superbubbles (Kavanagh 2020), and the characteristics of non-equilibrium ionisation plasmas (Breitschwerdt and de Avillez 2021). Next, there are contributions on simulations of cosmic ray propagation (Mertsch 2020), on their detection (Albrecht et al 2022) and what we can learn from that, on interstellar radioactive isotopes (Diehl 2021), and on observations of neutrinos (Kheirandish 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There are contributions on the production of cosmic ray (CR) electrons (Alsaberi et al 2019) and their transport (Heesen 2021) as deduced from observations, the generation of X-rays and cosmic γ -rays in interstellar shocks (Sano and Fukui 2021), the mechanism of particle acceleration via diffuse shock acceleration (Urošević et al 2019), the thermal and non-thermal X-ray emission from superbubbles (Kavanagh 2020), and the characteristics of non-equilibrium ionisation plasmas (Breitschwerdt and de Avillez 2021). Next, there are contributions on simulations of cosmic ray propagation (Mertsch 2020), on their detection (Albrecht et al 2022) and what we can learn from that, on interstellar radioactive isotopes (Diehl 2021), and on observations of neutrinos (Kheirandish 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is predicted that astrophysical neutrinos are produced in the highest energy extragalactic sources such as the super-massive black holes at the centre of active galactic nuclei [46,47], the collapse of massive stars in gamma ray bursts [48,49], or in star burst galaxies [50]. Although some potential points sources have been identified and there is growing evidence for the blazar connection [51,52], the exact nature of astrophysical neutrino sources remain uncertain [53][54][55][56][57][58][59][60][61][62].…”
Section: Neutrino Sourcesmentioning
confidence: 99%
“…To date diffuse Galactic neutrino emission has not been discovered (Aartsen et al 2017;Albert et al 2018), despite that it has been predicted to exist for decades (Stecker 1979;Kheirandish 2020, for a recent review) and studied in light of the IceCube measurements (Ahlers & Murase 2014;Anchordoqui et al 2014;Neronov et al 2014;Joshi et al 2013;Kachelrieß & Ostapchenko 2014;Spurio 2014;Gaggero et al 2015;Palladino & Vissani 2016;Denton et al 2017). In particular, primarily based on previous sub-PeV gammaray limits posed by the CASA-MIA (Borione et al 1998) and KASCADE experiments, Ahlers & Murase (2014) showed that the Galactic contribution to Ice-Cube neutrinos is subdominant (see also Murase et al 2016), and the GP may give ∼ 3 − 10% of the 10 − 100 TeV all-sky neutrino flux with E 2 ν Φ IC ν ∼ (5 − 10) × 10 −8 GeV cm −2 s −1 sr −1 (Aartsen et al 2015(Aartsen et al , 2020.…”
Section: Introductionmentioning
confidence: 99%